Densitas dan Fekunditas Cembirit (Tabernaemontana macrocarpa Jack.) di Komunitas Acacia auriculiformis A.Cunn.ex Benth di Hutan Lindung Mangunan, Bantul - Kusumadewi, Anindyasari; Sancayaningsih, Retno Peni (Universitas Sebelas Maret, 2016)
Acacia Community in the Conservation Forest of Mangunan has six vegetation species with four largest dominant, they are Acacia (Acacia auriculiformis), Cembirit (Tabernaemontana macrocarpa), Mahogany (Swietenia mahagony), and Sono (Dalbergia latifolia). In previous growthform analysis of A. auriculiformis, tree density was higher (380 ind Ha-1) compared to T. macrocarpa (280 ind Ha-1), but the sapling and seedling of A. Auriculiformis had lower density (20ind Ha-1 and 23.600 ind Ha-1) compared to T. macrocarpa (520 ind Ha-1 and 26.800 ind Ha-1). The presence of T. macrocarpa showed that there was an interspecies competition critically with the main community, A. auriculiformis. Therefore, the purposes of this research are to analyze the density of tree, sapling, and seedling growthforms of T. macrocarpa; to assess the fecundity of T. macrocarpa of 3 stem diameter classes. This research is the continuation of the previous research in 2015. Data collection had been conducted in December 2015-February 2016 in Conservation Forest Mangunan, Bantul. Serial observations were conducted six times in five permanent plots of 10x10 m2. The growth data were analyzed using Relative Growth Rate (RGR) analysis. Results of this research show that T. macrocarpa density from tree, sapling, and seedling growthforms are 480 ind Ha-1, 860 ind Ha-1, and 30.200 ind Ha-1. T. macrocarpa stands with smaller diameter have greater RGR value (0,00079 cm) than stands with larger diameter (0,00040 cm). The highest fecundity value of stands from the large, medium and, small stands diameter: 2,37%; 1,93%; and 1,16% respectively. The highest RGR, fecundity, and seedling density value of T. macrocarpa show an aggressive growth, thus, this species is estimated to threat or substitute the main species A. auriculiformis.Keywords: Density dan Fecundity of Tabernaemontana macrocarpa Jack., Acacia auriculiformis A.Cunn.ex Benth Community, Conservation Forest of Mangunan.Â